(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Non-traditional vegetable crop of the medium variety Bayrampasa artichoke, created in Turkey on plots 90x30, 90x50, 90x70, 90x90 cm - 37.0 - 22.2 - 15.8 - 12.3 thousand plants per hectare and plant growth, development, productivity and The economic efficiency of cultivation technology has been studied. When planting the Bayrampasa variety on an area of 90x50 cm with a density of 22.2 thousand seedlings per hectare, the first fruits ripen 2-6 days earlier compared to all options, on average 576 grams per plant, 182-183 grams 3.2 3, 3 pcs. fruit (baskets) were formed. The yield is 18-52% higher than all options, 1 kg of product is the cheapest (5499 soums), the profitability indicator (263.7%) is 6-177% higher than all options.